BHINNEKHA TUNGGAL IKA: KHASANAH MULTIKULTURAL INDONESIA DI TENGAH KEHIDUPAN SARA - Gina Lestari (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: High degree of diversity in Indonesia is an axis that easily burned by confrontation of identity (tribes, religion, and race). That’s why comprehensive understanding regarding Indonesian diversity is needed. Study about culture diversitynot only gives us comprehensive picture but more to that, it can raise dialogue about Indonesia unity in diversity. Multiculturalism was given, but Bhinneka Tunggal Ika (unity in diversity) was heritage that need to be preserved.Keywords : Bhinneka Tunggal Ika, multicultural